Respuestas

2013-06-06T00:19:42+02:00
1)                                                2) 
x+3y=10                                             7x+3y=6 *¨4   
2x+y= 5 *3                                          2x-4y=26 * 3

 x+3y=10                                            28x+12y=24                                                              
-6x-3y=-15                                             6x-12y=78
-5x //  = -5                                             34x //=102
     x= -5/-5                                                   x = 102/34
     x=1                                                         x=3

reemplazando:                                              reemplazando:  
x+3y=10                                                        7x+3y=6
1+3y=10                                                        7*(3) +3y= 6
    3y=10-1                                                        21 +3y=6
      y= 9/3                                                               3y= 6-21
       y=3                                                                    y= -15/3
                                                                                 y= -5

 comprobación:                                               comprobación: 
 x+3y=10                                                       7x+3y=6
1+3*(3)=10                                                     7*(3)+3(-5)=6
1+  9   =10                                                         21 -15= 6
     10 = 10                                                                6 = 6